THE RISKS OF DECENTRALIZATION REFORM AND THE METHODS OF SOLVING THEM - Yemelyanov, Volodymyr; Sokirko, Mikhail (Public Administration and Regional Development, 2020)
The article is devoted to analyzing the possible risks of decentralization reform and finding ways to address and reduce them. Being in the unfinished stage, decentralization is an important systemic reorganization that consecuent the security, development and economic recovery at the local and national levels. Systemic changes at the local level in times of economic and political instability require careful and prudent public policy. The main risks that threaten the reform and the danger of Ukraine's sovereignty, separatism, centrifugal tendencies, enclave, criminalization have been identified. Particular risk is the possible separatism in certain regions of the state. The volatile political situation, both at the national and especially at the local level, threatens to reform decentralization and local government performance. The questions of linguistic and ethno-national factors and their role in the formation of united communities are investigated. The methodological and regulatory arrangements for decentralization are important and relevant to the realities of community association. The proposed amendments to the Constitution of Ukraine regarding decentralization and their risks are analyzed. Legality and the rule of law are a prerequisite for preventing the risks of decentralization and for the development of united communities. The role of prefects in overseeing the legality of decisions of local self-government bodies with the possibility of violation of the functional balance of the judicial branch is considered. Possible preventive ways of reducing the risks and challenges of reform, addressing topical reform issues, and promoting state-building are suggested. The article explores the linguistic issue of national minorities and expresses the opinion on the importance of the national language as a unifying and state-building factor.